Fully Coupled Fluid-Structure Algorithms for Aeroelasticity and Forced Vibration Induced Flutter: Applications to a Compressor Cascade - Leyland, Penelope; Carstens, Volker; Blom, Frederic; Tefy, Tiana (European Journal of Computational Mechanics, 2000)
Algorithms for Fluid-Structure Coupling techniques are investigated in the time domain. The accurate prediction of the interaction requires consistency of the interface boundary conditions with the time levels of integration of the fluid and the structure equations. If staggered algorithms are used, the time delay causes non-physical energy dissipation in the system which modifies the calculated aeroe/astic behaviour. In order to be compatible, the equations must be integrated simultaneously and implicitly. These techniques are tested on a standard aeroelastic airfoil problem, and then applied to the direct coupling of an assembly of 20 compressor blades performing torsional vibrations.